HUBUNGAN AKSEPTOR KB HORMONAL DENGAN KEJADIAN AMENORRHEA DI PUSKESMAS BOJONG KECAMATAN BOJONG KABUPATEN TEGAL TAHUN 2009 - Siswati . (LPPM Universitas Pekalongan, 2011)
According to Department of Planning and community family welfare Tegal regency amount akseptor KB hormonal Public Health Center Bojong in the year 2008 is 1046 with Akseptor details akseptor needle 726 KB akseptor, implan 217 akseptor, 103 pills. From the results of the observation in the study of health Bojong KB hormonal use was much the occurrence of amenorrhea is 57 akseptor, so researchers are interested to take this case. This study aims to find out the KB akseptor incident amenorrhea with hormonal health Bojong in 2009. Design research is a study observational with cross sectional approach. Respondents who examined the health Bojong in 2009 amounted to 105 respondents. Data of respondents who experienced amenorrhea incidence obtained with the distribution of the questionnaire as a data collection instrument is the subject of research akseptor KB hormonal events that experienced amenorrhea. Research in Public Health Center Bojong year 2009, was from 105 respondents who experienced amenorrhea incidence of 54.3% and 45.7% non amenorrhea. Side effects are influenced by the hormone progestin in the hormonal contraceptive. This indicates a relationship with the occurrence KB hormonal amenorrhea respondents who use hormonal KB most experienced amenorrhea incidence of the 57 respondents (54, 3%). Midwives are expected to provide IEC about the factors that influence the occurrence Akseptor KB amenorrhea after hormonal and hormonal KB for the user are expected to visit after the re-use hormonal KB.